2006
DOI: 10.1136/jcp.2005.026831
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 expression correlates with poor prognosis in pancreatic cancer

Abstract: Background: Cyclooxygenase-2 (COX-2) overexpression is related to poor outcome in several cancers. COX-2 is upregulated in 42-90% of pancreatic ductal adenocarcinomas and is a potential target for chemotherapy. Earlier studies have not shown the expression of COX-2 to be a prognostic factor in pancreatic cancer. Objective: To evaluate the prognostic value of COX-2 in a series of patients with pancreatic adenocarcinoma. Methods: 128 patients operated on for pancreatic adenocarcinoma at Helsinki University Centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
3
4

Year Published

2006
2006
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 32 publications
(24 reference statements)
5
74
3
4
Order By: Relevance
“…After treatment cells were harvested and lysed, and equal aliquots of extracted protein were analyzed for Bcl-2 expression by Western blotting. The levels of β-actin were also measured as a normalization control 2002; Juuti et al, 2006). Although COX-1 is present at a constant level in most cells and tissues, previous studies have shown that COX-1 is highly expressed in several types of tumors,including breast cancer (Chulada et al, 2000;Kirschenbaum et al, 2000;Connolly et al, 2002;Sales et al, 2002;Gupta et al, 2003;Daikoku et al, 2005;Daikoku et al, 2006;Daikoku et al, 2007;Erovic et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…After treatment cells were harvested and lysed, and equal aliquots of extracted protein were analyzed for Bcl-2 expression by Western blotting. The levels of β-actin were also measured as a normalization control 2002; Juuti et al, 2006). Although COX-1 is present at a constant level in most cells and tissues, previous studies have shown that COX-1 is highly expressed in several types of tumors,including breast cancer (Chulada et al, 2000;Kirschenbaum et al, 2000;Connolly et al, 2002;Sales et al, 2002;Gupta et al, 2003;Daikoku et al, 2005;Daikoku et al, 2006;Daikoku et al, 2007;Erovic et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although the patients groups in these studies are larger than in our study, the methodological differences in the selection of patients and / or immunohistochemical techniques employed, raise some doubts on the results of these studies. In the study of Juuti 102 , more than 30 years old specimens were included. It is well known that for immunohistochemical staining protocol, aging of the fixed tumour tissue might interfere with staining process 168 .…”
Section: Cox-2 Expressionmentioning
confidence: 99%
“…Tumors likely to be Cox-2 positive and defective in the p16/Rb pathway were included. 51,52,15 Other oncological treatments were not administered concurrently. Exclusion criteria were organ transplant, HIV, severe cardiovascular, metabolic, or pulmonary disease (for example, symptomatic coronary heart disease, uncontrolled blood pressure).…”
Section: Patientsmentioning
confidence: 99%